2020
DOI: 10.3390/ani10040714
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomic Effects of Long-Term Grape Pomace Supplementation in Dairy Cows

Abstract: The increasing demand for more animal products put pressure on improving livestock production efficiency and sustainability. In this context, advanced animal nutrition studies appear indispensable. Here, the effect of grape pomace (GP), the polyphenol-rich agricultural by-product, was evaluated on Holstein-Friesian cows’ whole-blood transcriptome, milk production and composition. Two experimental groups were set up. The first one received a basal diet and served as a control, while the second one received a 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 95 publications
(131 reference statements)
1
13
1
Order By: Relevance
“…The increase in specific circulating antibody titers observed in heifers supplemented with a RPGE is in accordance with other research where the effect of a long-time supplementation with grape pomace in dairy cattle (inclusion level: 5% of the total daily ration) was studied ( Pauletto et al, 2020 ). The authors reported that the supplementation had a positive impact on immunity-related gene expression.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The increase in specific circulating antibody titers observed in heifers supplemented with a RPGE is in accordance with other research where the effect of a long-time supplementation with grape pomace in dairy cattle (inclusion level: 5% of the total daily ration) was studied ( Pauletto et al, 2020 ). The authors reported that the supplementation had a positive impact on immunity-related gene expression.…”
Section: Discussionsupporting
confidence: 90%
“…Whilst, to the best of our knowledge, this other work is the sole reported study of grape polyphenols’ effect on ruminants’ immunity, several studies have been carried out on the effect of grape polyphenols on monogastric immune response. Interestingly, the low inclusion dose used in the present study, corresponding to 400 mg of total polyphenols/head/day, still induced a positive effect on the humoral response, despite being much smaller than the 23.4 g total polyphenol intake/day from a supplementation with grape pomace observed in this reported other work (19.5 kg DMI with 7.5% GP at 1.6% total polyphenols, ( Pauletto et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Specifically, the main finding of this study concerns the fact that dietary OL supplementation was shown to be effective in modifying the gene expression of lactating Saanen goats. This datum is therefore in a condition of affinity with what has already been shown in recent studies in which the enrichment of ruminants’ diet with plant matrices led to changes in the transcription process of specific genes [ 16 , 18 , 27 ]. The aspect that in any case must be immediately highlighted concerns the fact that generally, the RNA-seq approach on whole blood is capable of highlighting variations of expression that involve entire gene clusters and not only a few transcripts or even one, just like in our case.…”
Section: Discussionmentioning
confidence: 54%
“…In this study, we decided to investigate the peripheral blood of goats fed a dietary OL supplementation, since in previous nutrigenomic studies on ruminants, it was possible to identify differentially expressed genes with extreme sensitivity and accuracy [ 16 , 18 , 27 ]. In addition to this, the characterization of gene expression carried out on blood tissue allows us to collect information capable of reflecting the molecular and biochemical mechanisms occurring in other tissues or organs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%